Satisfaction residents Kota Samarahan toward Kentucky Fried Chicken at Samarahan / Nurasyura Mohamad@Othman - Mohamad@Othman, Nurasyura (Faculty of Business and Management, Universiti Teknologi MARA, 2016)
The level of competitiveness that have in the global market may cause every company to achieve the level of satisfaction that every consumers want. It is included in the fast foods industry. So the great level of performance are required for every one to compete. Including at the KFC outlet at Samarahan, the residents of Kota Samarahan that include as the highest number of consumers that will came to the outlet. Specifically, this study focuses on the satisfaction residents Kota Samarahan towards Kentucky Fried Chicken (KFC) outlet at Samarahan. The purpose of this study is to know what are the factor that can lead us for satisfying the residents at Kota Samarahan either from the factor perceived value, core quality and relational quality and how to improve their performance that are required by the customers. Primary data for the study was collected by means of self-administrated questionnaire and supported by sufficient number of secondary data from previous thesis, journal and books. For the purpose of this study, self-administrated questionnaire were collected from 384 consumers at Kota Samarahan.